CLAY MINERALS AS DYNAMIC TRACERS OF SUSPENDED MATTER DISPERSAL IN THE GULF OF CADIZ (SW SPAIN) - Gutiérrez-Mas J.M.; López-Aguayo F.; Achab M. (My University, 2006)
The dispersal of suspended matter in the Gulf of Cadiz (SW Spain) is related to its geographical position near the Strait of Gibraltar, and the continental margin, and to Atlantic and Mediterranean water flows and their interaction with the littoral tidal processes. The main direction for transport of suspended matter is towards the southeast, along the continental margin, from the mouths of the rivers Guadiana and Guadalquivir to the Mediterranean. This general transport pattern is perturbed by littoral processes such as those occurring in Cadiz Bay, where a portion of Atlantic suspended matter, driven by flood tide, comes into the inner bay and is deposited in the shallow waters of lagoons and salt marshes. Subsequently, because of the southeast wind and waves, these sediments are remobilized and transported to the west by the ebb tide, to deeper Atlantic waters. This dynamic interaction between Atlantic and littoral waters generates a different type of sediment layout, the origin of which is difficult to establish. In order to understand the dispersal of the suspended matter and its effects on the inner continental shelf, the distribution of the main clay minerals has been determined by means of X-ray and Q-mode and R-mode factor analysis. The suspended matter dispersal paths were established through the distribution of main clay mineral associations and from the ratios amongst these minerals. The results allow us to determine the importance of the tidal flows in the suspended matter transport system of the Gulf of Cadiz. Therefore, a record was kept of which of the outgoing tidal flows from the inner parts of Cadiz Bay reached the continental shelf. The flows intercept the clear Atlantic waters giving rise to a complex sediment distribution and to the mix of clay minerals. The study has also allowed us to establish the sediment source areas and the extent of sediment transport and the paths they follow. © 2006 The Mineralogical Society.
Keywords: CLAY MINERALS; GULF OF CADIZ; SEDIMENTARY DYNAMIC; SPAIN; SUSPENDED MATTER FLOW